Mahatma Gandhi and India's independence in world history - Malaspina, Ann, 1957- (Berkeley Heights, NJ : Enslow Publishers, 2000)
Traces India's struggle to gain independence, highlighting the life and leadership of Mohandas Gandhi whose tactics of nonviolent protest have become a goal of resistance movements worldwide.
Includes bibliographical references (p. 126) and index.
Keywords: Gandhi, -- Mahatma, -- 1869-1948 -- Juvenile literature; Gandhi, -- Mahatma, -- 1869-1948.; Nationalists -- India -- Biography -- Juvenile literature; Statesmen -- India -- Biography -- Juvenile literature; Statesmen; India -- Politics and government -- 1919-1947 -- Juvenile literature; India -- History -- Autonomy and independence movements -- Juvenile literature; India -- Politics and government -- 1919-1947.; India -- History